The Relationship of Stress with the Degree of Morning Sickness in 1st and 2nd Trimester Pregnant Women - Ekawati, Heny; Martini, Diah Eko; Rohmawati, Aulia Rifna (Universitas Muhammadiyah Lamongan, 2022)
Introduction Morning sickness is a common problem that occurs in pregnant women. This condition can cause nutritional and comfort problems for pregnant women. In fact, many pregnant women experience morning sickness. This study aims to determine the relationship between stress and the degree of morning sickness in pregnant womenMethods: This study used a cross sectional research design the sample was taken using the Total Sampling technique, the instrument used was a questionnaire. The data were analyzed using the Spearman rank test.Results: The results showed that almost half of pregnant women who experienced morning sickness experienced moderate stress, namely as many as 13 (43.3%) pregnant women, and some other pregnant women who experienced morning sickness experienced severe stress as many as 2 (6.7%) pregnant women. Based on the results of calculations using the Spearman rank test (rho) that the significance value is 0.000 where the value (p <0.05), which means that there is a relationship between stress and the degree of morning sickness in pregnant women..Conclusion: There is a relationship between stress with the degree of morning sickness in the Ist and 2nd trimestersKeywords: stress, degree of morning sickness,Pregnancy